How do stroke survivors with communication difficulties manage life after stroke in the first year? A qualitative study. Issue 5 (4th July 2019) - Wray, Faye; Clarke, David; Forster, Anne
Abstract: Background: Interest in how stroke survivors might be better supported to manage life after stroke has grown rapidly in recent years, with a particular emphasis on enabling 'self‐management'. Post‐stroke communication difficulties may pose a unique barrier to longer term adaptation and adjustment. It is important to understand how stroke survivors with communication difficulties manage life after stroke and what support may be needed to facilitate this process. Aims: To explore how stroke survivors with communication difficulties manage life after stroke in the first year. Methods & Procedures: A cross‐sectional qualitative study involving in‐depth semi‐structured interviews with stroke survivors with communication difficulties (aphasia, dysarthria or apraxia of speech) and/or their family members at single time points during the first year post‐stroke. A total of 21 participants (14 stroke survivors and seven family members) took part in interviews for the study. Interview data were analysed using thematic analysis. Outcome & Results: A total of six themes were identified: (1) strategies to manage changes to communication; (2) testing communication outside of the home; (3) balancing support and independence; (4) hope for recovery; (5) obtaining support from healthcare professionals; and (6) adapting activities and keeping busy. Stroke survivors with communication difficulties and their family members undertook significant work (practical, relational, emotional) to manage their condition. Adaptation and adjustment was often facilitated by 'doing'; testing out which activities could be managed independently and which required additional support. Some stroke survivors and their family members demonstrated considerable resourcefulness and creativity in developing strategies to manage their communication difficulties. Despite the work undertaken, many expressed a lack of confidence in their ability and feelings of powerlessness and abandonment at the point of discharge from community services. Conclusions & Implications: Stroke survivors and their family members develop personally meaningful and context‐specific strategies to adjust to and manage life after stroke. Future interventions should recognize, support and build upon the active work already undertaken by stroke survivors with communication difficulties and their families. Further support before and around the point of discharge from community services may be needed to help build confidence and skills to manage in the longer term. The benefit of a supported self‐management approach for stroke survivors with communication difficulties should be further investigated.